Peningkatan Prestasi Belajar Perubahan Energi Listrik Melalui Metode Demonstrasi dan Eksperimen Siswa Kelas VI SDN 1 Bayung Lencir Tahun Pelajaran 2024/2025 - Ariyani; Hadiyanyo; Indryani (Universitas Muhammadiyah Kuningan, 2025)
To create quality education in the future, education in Indonesia should pay more attention to the quality of education. For example, prioritizing teacher abilities, a good educational curriculum, then thinking about creating outstanding students. The objectives of this research are: 1) To describe the increase in student learning achievement in learning changes in electrical energy through the Demonstration and Experiment Method, 2) To find out how complete the students' learning is in learning changes in electrical energy after using the Demonstration and Experiment Method. This research uses demonstration and experimental methods with the Kemmis and Taggart model of classroom action research (PTK) approach which consists of four stages: planning, action, observation and reflection. The research was conducted at SDN 1 Bayung Lencir on 20-28 October 2024, involving 38 students (11 boys and 9 girls). Data is collected through observation, learning results tests, and documentation, then analyzed using observation techniques, evaluation of test results, and documentation. From the results of this research, it was found that student learning achievement increased from each cycle, namely cycle I 50%, and cycle II 100%. This research shows that the application of the Demonstration and Experiment Method effectively increases student learning achievement in learning about changes in electrical energy. The results show an increase in student learning completeness from 50% in cycle I to 100% in cycle II. This proves that this method is able to help students understand concepts better through direct and interactive experience. The implications of this research are good for teachers, students and schools as well as other researchers.